Value of growth regulators in forming high indicators of productivity and quality of winter wheat grain - N. I. Mamsirov; A. A. Makarov (Новые технологии, 2019)
One of the most important elements of modern agricultural technologies in Agriculture is the use of biological products and growth regulators of agricultural plants, which can positively affect the metabolic processes in plants in small doses and lead to significant positive changes in the processes of growth and development of cultivated field crops. Practical significance of these preparations is determined, first of all, by their effect and degree of influence on the processes of plant development at different stages of ontogenesis, and the ability to significantly accelerate the growth or increase the yield of most crops. At the same time, the use of biological products and growth-regulating drugs is considered as an environmentally friendly and cost-effective way to increase the productivity of crops, contributing to a more complete realization of the potential of plants, including winter wheat.The article presents the results of the study on the influence of Bigus and Melafen growth regulators on the yield and grain quality of winter wheat varieties of Vostorg and Gracia selected by FSBSI “KSC named after P.P. Lukyanenko” taking into account specific soil and climatic conditions. In the research the stimulating effect of Bigus and Melafen preparations on growth processes and formation of generative organs of plants has been established, and as a result, a positive effect in the form of an increase in winter wheat grain yield.